PENGARUH INKLUSI KEUANGAN, LITERASI KEUANGAN, FINANCIAL TECHNOLOGY TERHADAP KINERJA UMKM FURNITURE DI KECAMATAN KARANG BAHAGIA CIKARANG - Wisnu Setyawan; Mita Amelia (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The development of micro, small and medium enterprises (MSMEs) currently needs to be increased through knowledge of financial literacy and business experience that has been passed as material for consideration in making financial decisions in the future to maximize business growth. This growth has also spawned several innovations such as financial inclusion, financial literacy and technology to facilitate public access through financial services. This study aims to obtain data on the effect of financial inclusion on MSME performance, the effect of financial literacy on MSME performance, and the effect of financial technology on MSME performance. The data used in this study is primary data obtained from distributing questionnaires to 52 MSMEs in Karang Bahagia village, KarangBahagia District, Bekasi Regency. The hypothesis used is multiple regression with the help of SPSS. This study shows that there is only one variable that has a significant effect, namely financial literacy on the performance of MSMEs. And there are two variables that have no significant effect, namely financial inclusion on MSME performance and financial technology on MSME performance.